(untitled) (Global Journal of Science Frontier Research, 2021)
This study was conducted to phenotypically characterize the local cattle population under farmers’ management conditions. Field studies and collection of data carried out through household survey, focus group discussions, and linear body measurements of sample cattle. A total of 180 households were randomly selected for household interview and 345 cattle were sampled for morphological characterization. Indigenous cattle have variable coat color types, and the most dominant were plain (56.7%), patchy (31.2%), and spotted (11.6%). The frequently observed coat color types are light red, dark red, and black. Body measurements of indigenous cattle are significantly (P≤0.01) affected by sex and location and, found to be higher in male animals and hotter environments. In male cattle between HG and BL, the linear body measurements show a strong positive correlation (r=0.71). Average daily milk yield, lactation yield, and lactation length were significantly (P ≤0.01) higher in highlands areas. Age at first calving (53months) was also shorter in highland. The criteria used for the selection of breeding animals by the community are high milk yield, fertility, and body size. Phenotypic results of the highland cattle populations varied from the midland and lowland location and, therefore, to put specific characteristics’ of the cattle type, further molecular characterization, and productivity evaluation is needed.